The Stability of Fluctuation Immigration Effect on Two Species Prey-Predator System with Holling Type II Functional Response (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines the fluctuation immigration effect on the dynamic behavior ofthe prey-predator system, with Holling type II functional response. The mathematical techniqueto formulate and combine the effect of fluctuating immigration with the prey-predator systemwas provided. the result of this combined is a non-autonomous system. In order to convert it toan autonomous system, we propose an approximated technique for facilitating mathematicalanalysis. This system has been examined for local and global stability. as well, it is tested usingKolmogorov criteria in order to verify the susceptibility to coexistence and extinction.